On fuzzy semi-connectedness - Chaudhuri, A.K.; Das, P. (Universiti Kebangsaan Malaysia, 1996)
The concepts of fuzzy semi-open and semi-closed sets have been utilised to define four types of semi-separation of fuzzy sets corresponding to the notions of separation, Q-separation, weak separation, strong separation and eight types of semi-connectedness viz SiC, SCi-connectedness for i = 1 ,2 ,3 ,4 corresponding to the notions of O-connectedness, connectedness, Oq-connectedness and ci-connectedness of a fuzzy set. Interrelationship between these notions of semi-connectedness of a fuzzy set and their properties have been discussed.